Methodological Foundations Of Communicative Creativity System Development Among University Students - V. Lesher, Olga (Revista San Gregorio, 2019)
In modern society and in all areas of professional activity, they increase the role of communication, the specificity and course of communicative processes, and, accordingly, the requirements for their participants. In this regard, the problem of students' communicative creativity development at the stage of vocational training at a university is being updated. It should be noted that at present, due attention is not paid to this aspect of vocational training of students in technical areas neither in theory nor in the practice of vocational education. The article discusses the methodological foundations of communicative creativity system development for university students, interpreted as a set of interconnected and interdependent components that represent a certain integrity, based on the use of a set of scientific approaches: systemic, participatory and discursive, implemented on the basis of the principles of cognitive content transformation into emotional, free communication choice, and creative behavior social reinforcement. The scientific approaches considered in the article were the methodological foundations of a system development for the formation of communicative creativity among university students. The materials of the article are of practical value for organizing the training process in the context of students' communicative creativity development.